Silver-Treated Sutures for the Prevention of Biofilm-Associated Surgical Site Infections - Federica Paladini; Angelica Panico; Annalia Masi; Francesca Russo; Alessandro Sannino; Mauro Pollini (Antibiotics)
Background/Objectives: The huge concerns associated with biofilm-related infections in surgical procedures, along with the antibiotic resistance demonstrated by an increasing number of bacteria, have highlighted the need for alternative and effective prevention approaches. The aim of this research was to develop novel antimicrobial coatings on surgical sutures for the prevention of surgical site infections through nanotechnology-based methods. Results: The results demonstrated that although very low amounts of silver precursor were adopted for the treatments, the silver coating was effective against Staphylococcus aureus and antibiotic-resistant Pseudomonas aeruginosa in reducing the potential risk of infection. Methods: Nanostructured silver coatings were deposited onto the surface of polyglactin 910 absorbable braided sutures through a technology based on a photo-assisted chemical reaction. The materials were characterized in order to verify the efficacy of the coating in preventing biofilm formation and in reducing the bacterial colonization of the device. Conclusions: As a broad-spectrum antimicrobial agent, silver represents an important option for the prevention and management of surgical site infections. The silver deposition technology adopted in this work provides an interesting strategy for preventing biofilm formation on medical devices such as surgical sutures.